2014
DOI: 10.3892/ijo.2014.2266
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of low expression of hMOF with clinicopathological features of colorectal carcinoma, gastric cancer and renal cell carcinoma

Abstract: Abstract. Human MOF (males absent on the first), as a histone acetyltransferase, is responsible for histone H4K16 acetylation in human cells. Recent studies have shown that the abnormal gene expression of hMOF is involved in certain primary cancers. Here, we first report the involvement of hMOF expression in clinically diagnosed primary colorectal carcinoma (CRC) and gastric cancer. Simultaneously, the correlation of hMOF expression and clinicopathological features in CRC, gastric cancer and renal cell carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 34 publications
0
47
0
Order By: Relevance
“…H4K16ac and MOF are known to be associated with tumorigenesis and heterogeneity [32,33]. We report for the first time that low-level MOF-induced downregulation of H4K16ac is a downstream target of Notch signaling in human HCC and breast cancer.…”
Section: Discussionmentioning
confidence: 82%
“…H4K16ac and MOF are known to be associated with tumorigenesis and heterogeneity [32,33]. We report for the first time that low-level MOF-induced downregulation of H4K16ac is a downstream target of Notch signaling in human HCC and breast cancer.…”
Section: Discussionmentioning
confidence: 82%
“…MOF plays important roles in transcription activation, DNA damage response, and maintenance of embryonic stem cell pluripotency (Gupta et al, 2005(Gupta et al, , 2014Li et al, 2010Li et al, , 2012Sharma et al, 2010). Compared with normal tissues, expression of MOF is frequently downregulated in several types of solid tumors (Cao et al, 2014;Liu et al, 2013;Pfister et al, 2008;Zhang et al, 2014). However, there are also reports that MOF expression is elevated in certain cancers and MOF may stimulate cell proliferation and transformation (Gupta et al, 2008;Zhao et al, 2013a).…”
Section: Introductionmentioning
confidence: 95%
“…In recent years, the effects of hMOF on the occurrence and development of malignant tumors has been a hot area of study in international academia. Previous studies indicated that hMOF is frequently downregulated in primary breast carcinoma and medulloblastoma (19), human renal cell (20), and colorectal carcinoma, and gastric cancer (23). However, the expression of hMOF was reportedly much higher in NSCLC compared to corresponding normal tissues, and hMOF promoted the proliferation, metastasis and adhesion of NSCLC cell lines (21).…”
Section: Discussionmentioning
confidence: 98%